DAYA TARIK VISUAL SEBAGAI BRAND RECALL PADA IKLAN TELEVISI (STUDI KASUS : IKLAN MIZONE 2012 VERSI âTILTâ) - Utama, Jiwa; Swasty, Wirania (LPPM STMIK STIKOM Indonesia, 2018)
The power of visual and audio messages on television commercial (TVC) is critical to create the advertised brand awareness. The use of popular songs as an advertisement attraction is often used in television commercials. This paper is a case study of Mizone TVC in 2012. The popular song should be able to help the visual appeal used in helping audiences remember brands and advertisements. This study aims to determine the role and impact of visual appeal on TVC that use popular song as the appeal of music to brand reminders. The method used in this study is based on marketing approach and advertisement evaluation research through advertising stimulus recall test method. The first stage is an audio stimulus test by playing a popular song from the case study. The second stage is a visual stimulus test by showing some advertising frames as a visual stimulus. The third stage is to show the ads as a whole to know the response about the attractiveness of the ad to brand recall. This method is tested on the respondent which is the target audiences of Mizone. The analysis of the visual stimulus visual recall shows the use of visual appeal not only from TVC talents but also through advertising messages packaged with unique, distinct visual approaches and identity that can help audiences to better remember the brand.